IgA Nephropathy Precedes the Onset of the Rheumatic Disease in a Female with Ankylosing Spondylitis - Haider M Al Attia; Mariano R Carballo (Rheumatica Acta: Open Access - Peertechz Publications, 2017)
IgA nephropathy (known as Berger's disease) is the most common cause of glomerulonephritis. Its estimated prevalence between 25-50 cases per 100.000 individuals. Gross hematuria (40-50%) and microscopic hematuria (30-40%) are the most common fi ndings which can be related to upper respiratory tract or gastrointestinal infection. Between 15-40% of affected individuals may progress to chronic renal failure [1-5]. The defi nitive diagnosis is made by renal biopsy fi ndings which is characterized by  mesangial IgA deposition. Although the condition is a limited non-systemic renal disease, some systemic diseases are sporadically associated with mesangial IgA deposition. Henoch-Schonlen purpura (HSP), systemic lupus erythematosus (SLE), hepatitis, dermatitis herpetiformis, celiac disease and ankylosing spondylitis ( AS) have been closely linked to the IgA nephropathy [6,7].